Higher cortical deficits influence attentional processing in dementia with Lewy bodies, relative to patients with dementia of the Alzheimer's type and controls. Issue 10 (13th June 2006) - Bradshaw, J M; Saling, M; Anderson, V; Hopwood, M; Brodtmann, A
Abstract : Background: Attentional dysfunction is believed to be a prominent and distinguishing neuropsychological feature of dementia with Lewy bodies (DLB); yet, the specific nature of the attentional deficit and factors that can potentially influence attentional processing in DLB have not been fully defined. Aims: To clarify the nature of the attentional deficit in early-stage DLB relative to patients with early-stage dementia of the Alzheimer's type (DAT) and elderly controls, and examine the effect of task complexity and type of cognitive load on attentional processing in DLB. Methods: Attentional impairment and fluctuating attention were investigated in three groups of subjects—patients with clinical features of early probable DLB (n = 20), a group with early probable DAT (n = 19) and healthy elderly controls (n = 20)—using an experimental computerised reaction time paradigm. Results: Patients with DLB showed greater attentional impairment and fluctuations in attention relative to patients with DAT and elderly controls. The attentional deficit was generalised in nature but increased in magnitude as greater demands were placed on attentional selectivity. Attentional deficits in DLB were most pronounced under task conditions that required more active recruitment of executive control and visuospatial cognitive processes. Conclusions: Attentional deficits in DLB are widespread and encompass all aspects of attentional function. Deficits in higher cortical function influence the degree of attentional impairment and fluctuating attention, suggesting that attentional processing in DLB is mediated by interacting cortical and subcortical mechanisms. These findings serve to clarify the nature of the attentional deficit in DLB and have potentially important ramifications for our understanding of the neurocognitive underpinnings of fluctuations.